Hukum Keluarga Islam Dan Hak Warga Negara: Analisis Polemik Perlindungan Hak Anak Luar Nikah - Abdullah Sani, Azhar, Suaib Lubis, (Pusdikra Publishing, 2023)
In family life, marriage and the birth of children are major events that give rise to complex legal consequences that will remain attached to the human being until death. Indonesia as a rule of law has guaranteed and protected the fulfillment of the constitutional right to marriage for all Indonesian citizens, as stated in Article 28B paragraph (1) of the 1945 Constitution of the Republic of Indonesia which reads: